152k views
1 vote
Show, using implicit differentiation, that any tangent line at a point P to a circle with center O is perpendicular to the radius OP.

User WENDYN
by
5.2k points

1 Answer

2 votes

A circle centered at
O(a,b) with radius
R (the length of
OP) has equation


(x-a)^2+(y-b)^2=R^2

which can be parameterized by


\vec c(t)=\langle x(t),y(t)\rangle=\langle a+R\cos t,b+R\sin t\rangle

with
0\le t\le2\pi.

The tangent line to
\vec c(t) at a point
P(x_0,y_0) is
(\mathrm dy)/(\mathrm dx) with
x=x_0 and
y=y_0. By the chain rule (and this is where we use implicit differentiation),


(\mathrm dy)/(\mathrm dx)=((\mathrm dy)/(\mathrm dt))/((\mathrm dx)/(\mathrm dt))=(R\cos t)/(-R\sin t)=-(\cos t)/(\sin t)

At the point
P, we have


x_0=a+R\cos t\implies\cos t=\frac{x_0-a}R


y_0=b+R\sin t\implies\sin t=\frac{y_0-b}R

so that the slope of the line tangent to the circle at
P is


(\mathrm dy)/(\mathrm dx)=-\frac{\frac{x_0-a}R}{\frac{y_0-b}R}=-(x_0-a)/(y_0-b)

Meanwhile, the slope of the line through the center
O(a,b) and the point
P(x_0,y_0) is


(b-y_0)/(a-x_0)

Recall that perpendicular lines have slopes that are negative reciprocals of one another; taking the negative reciprocal of this slope gives


-\frac1{(b-y_0)/(a-x_0)}=-(a-x_0)/(b-y_0)=-(x_0-a)/(y_0-b)

which is exactly the slope of the tangent line.

User Aukaost
by
4.6k points